Pengaruh Kualitas Produk dan Harga Terhadap Kepuasan Pelanggan Mie Gacoan Pahlawan Revolusi Jakarta Timur - Ardiansyah Saputra (Jurnal Bisnis Kreatif dan Inovatif, 2025)
In the current era of globalization, the business world is experiencing rapid growth, particularly in the culinary industry. This business is directly related to the basic human need for food, which is one of the fundamental necessities for survival. The influence of product quality and price on customer satisfaction at Mie Gacoan Dr. Mansyur Medan has become an interesting topic for research, considering the critical role these two factors play in maintaining and enhancing customer satisfaction. Customer satisfaction is crucial for ensuring repeat customers and building brand loyalty, which is particularly important in the highly competitive food industry. This study aims to determine the extent to which product quality and price affect customer satisfaction at Mie Gacoan in Medan, focusing on students of the Business Administration Department at Politeknik Negeri Medan as the research subjects. This study employs a quantitative research method with a descriptive approach, including tests for validity and reliability, classical assumptions, and hypothesis testing. The hypothesis testing includes t-tests, F-tests, and an analysis of the coefficient of determination (adjusted R square). By understanding the relationship between product quality, price, and customer satisfaction, this research aims to provide valuable insights for improving service strategies and pricing models in the culinary business, ultimately helping Mie Gacoan improve its customer satisfaction and competitive edge in the market.